Transforming Arabic Language Learning through Product-Based Differentiated Teaching Modules: An Innovative Approach to Improving Learning Outcomes - Kurniya Khurotin, Laila; majid, abdul; aulia rahman, Rifqi (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This study aims to: (1) examine the implementation of product-based differentiated instructional modules in improving Arabic learning outcomes; (2) identify the improvement in students’ Arabic learning after using the product-based differentiated modules; and (3) test the effectiveness of these modules in enhancing Arabic learning outcomes. Using a quantitative experimental design, the study involved two classes: an experimental class and a control class. Both classes were given a pretest before instruction. The experimental class received instruction using the product-based differentiated module, while the control class was taught through conventional methods. Posttests were administered to both classes, and data were analyzed using t-tests and N-gain scores to evaluate learning improvement and module effectiveness. Results showed that the product-based differentiated module increased student engagement, interest, and motivation by incorporating varied activities such as discussions, presentations, and dialogue practice tailored to students’ learning styles and interests. Furthermore, students’ learning outcomes significantly improved in the experimental class, with an N-gain of 0.751 (high category) and an average score increase from 70.83 to 92.73, compared to the control class’s increase from 57.13 to 67.87. Thus, the product-based differentiated instructional module is effective in enhancing Arabic learning outcomes.